Experimental evaluation of physicochemical properties and tapping torque of hexagonal boron nitride in modified jatropha oils-based as sustainable metalworking fluids - Talib, N.; Rahim, E.A. (ScienceDirect, 2018)
In consideration of the important role of environmentally begin metalworking fluid (MWF) in the machining industry, jatropha oil has been acknowledged as a suitable type of lubrication based oil. Despite its advantages, crude jatropha oil (CJO) had its main drawback in terms of poor thermaloxidative stability due to the presence of unsaturated molecules that leads to oxidation reaction. The objective of this study was to evaluate the physicochemical properties and tapping torque of newly developed modified jatropha oils (MJOs). Initially, CJO was chemically modified through the transesterification process at various molar ratios of jatropha methyl ester (JME) to trimethylolpropane (TMP) to produce a series of MJOs denoted as MJO1, MJO3, and MJO5. Hexagonal boron nitride particles at concentrations of 0.05, 0.1 and 0.5 wt% were mixed with the MJOs. MJOs with and without hBN particles were analysed based on the physicochemical testing (i.e., acid value, viscosity, viscosity index (VI) and flash point) and tapping torque test (i.e., tapping torque, thrust force and tapping torque efficiency). Experimental results showed an improvement of physicochemical properties of these newly developed MWFs with the increase in JME:TMP molar ratio and concentration of hBN particles. MJO5 displayed the best physicochemical properties with the highest VI of 196, compared with MJO3 and MJO1. The addition of 0.5 wt% of hBN particles in MJO5 (MJO5c) caused the highest VI achieved at 228, compared with the other samples. The average tapping torque and thrust force were reduced approximately by 15% and 45%, respectively using MJO5a (0.05 wt% of hBN particles with MJO5), compared with SE. MJO5a also demonstrated an improvement of 118% tapping torque efficiency that indicated an excellent machining performance. In conclusion, MJOs containing hBN particles showed better performances on the lubricating property. Among the samples, MJO5a could be proposed to substitute synthetic ester as a sustainable MWF for machining processes